Systematic analysis of Baobaoqu fermentation starter for Wuliangye Baijiu by the combination of metagenomics and metabolomics - Zhang, Qingmei; Du, Guocheng; Chen, Jian; Li, Jianghua; Qiao, Zongwei; Zheng, Jia; Zhao, Dong; Zhao, Xinrui (Frontiers in Microbiology, 2022)
Baobaoqu (BBQ) is a traditional fermenting power, which is widely applied in Nong-flavor Baijiu brewing. There are two different types of BBQ (premium BBQ and normal BBQ) used in industrial manufacture, but the reasons for the significant differences between two kinds of BBQ have not been clearly illuminated. In this study, the combination of metagenomics and metabolomics was performed to compare the differences in the composition of microbial communities and the components of flavors between premium BBQ and normal BBQ. The results showed that the glycosidase-producing microorganisms are the biomarkers of premium BBQ, contributing a better ability of carbon source utilization than normal BBQ. In addition, several important flavors (ethyl hexanoate, phenylethanol, ethyl acetate) were rich in normal BBQ, which have a significant positive correlation with the biomarkers (Lactobacillus and Pichia kudriavzevii) of normal BBQ. It suggests that the microbial community has an advantage in utilizing raw materials in premium BBQ, while the community was inclined to form flavors in normal BBQ. The differences between two types of BBQ at the microbial and flavor level have theoretical and practical guiding significance in the application of premium and normal BBQ and in the further improvements of taste and quality of Baijiu.